USC a universal stub compiler. - O'Malley, Sean (Computer communication review.)
USC is a new stub compiler that generates stubs that perform many data conversion operations. USC is flexible and can be used in situations where previously only manual code generation was possible. USC generated code is up to 20 times faster than code generated by traditional argument marshaling schemes such as ASN.1 and Sun XDR. This paper presents the design of USC and a comprehensive set of experiments that compares USC performance with the best manually generated code and traditional stub compilers.